Leadership and Innovation in Subnational Government : Case Studies from Latin America - Campbell, Tim; Fuhr, Harald (Washington, DC: World Bank, 2013)
This book is about inventing successes and good practices of governments that are "closer to the people." Numerous examples throughout Latin America indicate-often despite macroeconomic instability, high inflation, and strong top-down regulation-that subnational actors have repeatedly achieved what their central counterparts preached: sound policymaking, better administration, better services, more participation, and sustained economic development. But what makes some governments change course and move toward innovation? What triggers experimentation and, eventually, turns ordinary practice into good practice? The book answers some of these questions. It goes beyond a mere documentation of good and best practice, which is increasingly provided through international networks and Internet sites. Instead, it seeks a better understanding of the origins and fates of such successes at the micro level. The case studies and analytical chapters seek to explain: How good practice is born at the local level; Where innovative ideas come from; How such ideas are introduced in a new context, successfully implemented, and propagated locally and beyond; What donors can do to effectively assist processes of self-induced and bottom-up change.